Static and free vibration analysis of delaminated composite plates using secant function based shear deformation theory - Bhardwaj N.; Sinha A.; Abhijeet B.; Sahoo R. (My University, 2025)
In this work, the static and free vibration analysis of delaminated composite plates are studied. The secant function based shear deformation theory (SFSDT), is used for the analysis of multiple delaminated models. This theory exhibits a non-linear shear stress distribution and fulfills the traction-free boundary conditions at the top and bottom surfaces of the plates, hence there is no need for a shear correction factor. The finite element method, a numerical solution-based approach is used here considering an eight-noded isoparametric quadratic element. The investigation explores the effects of delamination size, position and stacking sequence on the flexural and dynamic characteristics of the composite plates. Additionally, other geometric factors such as delamination thickness and shape are investigated to understand their impact. The study aims to identify the optimal configurations that minimize the detrimental effects of delaminations. The results provide valuable insights into the static and free vibration behaviour of delaminated composite plates, contributing to design guidelines and optimization strategies for structurally sound and efficient composite structures. Overall, this research offers a comprehensive investigation of the static and free vibration analysis of delaminated composite plates, advancing knowledge in the field and facilitating improved design practices. © IMechE 2024.